Analyzing General Anti-Avoidance Rule (GAAR) Policy in Indonesia - Royani, Zulfa; Yulianti, Yulianti (E-Jurnal Akuntansi, 2024)
The GAAR provision to combat unacceptable tax avoidance has already been ratified in Law Number 7 of 2021 concerning the Law on Harmonization of Tax Regulations (HPP Law) and Government Regulation Number 55 of 2022 (PP 55/2022). Employing qualitative research with a case study approach, this study conducts literature studies and interviews with regulators in the Ministry of Finance and relevant stakeholders to determine the aspects that must be taken into Indonesian GAAR provision. This study found that GAAR provisions in Indonesia have fulfilled the three GAAR trigger elements. Using substance over form principle as GAAR has its challenges in regulation, infrastructure, and human resource. This GAAR implementation need to consider limits on authority and implementation procedures, the scope of tax avoidance, stages of formal and material testing, quality assurance mechanisms, and protection of taxpayers' rights. Keywords: Corporate Social Responsibility Disclosure; Profitability; Liquidity; Firm Value